The end of ethics and a way back : how to fix a fundamentally broken global financial system - Malloch, Theodore Roosevelt; Mamorsky, Jordan D. (Singapore : Wiley, 2013)
Bestselling author and professor Ted Malloch calls for real financial reform to restore confidence and fairness to a broken system From Ponzi schemes to the credit crisis to the real estate bubble, the financial industry seems to have lost its way on the road to riches. As private greed continues to undermine the public good, one might wonder what ever happened to business ethics. And how can we reform the global financial system to benefit everyone, rather than just the very lucky few?
pt. 1. Economic vice -- pt. 2. Recommendations.
Includes bibliographical references and index.
Keywords: Financial services industry -- Moral and ethical aspects; Financial services industry -- Management; Business ethics; BUSINESS & ECONOMICS -- Business Ethics; Business ethics; Financial services industry -- Management; Financial services industry -- Moral and ethical aspects; Electronic books